2016
DOI: 10.1080/09540121.2016.1178703
|View full text |Cite
|
Sign up to set email alerts
|

Perceived HIV risk, actual sexual HIV risk and willingness to take pre-exposure prophylaxis among men who have sex with men in Toronto, Canada

Abstract: Pre-exposure prophylaxis (PrEP) reduces HIV acquisition. Our goal was to determine the willingness of men who have sex with men (MSM) to take PrEP given perceived and actual HIV risk. HIV-negative MSM were recruited from September 2010 to June 2012 and asked about PrEP willingness and perceived HIV risk. Actual sexual HIV risk was measured by three condom-use components generated through principal components analysis. General HIV risk was measured using the HIV Incidence Risk Index for MSM (HIRI-MSM). Model 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(23 citation statements)
references
References 15 publications
2
17
0
Order By: Relevance
“…Many studies report challenges aligning perceived risk with actual risk [ 13 , 14 , 32 34 ]. Participants described concern regarding perceived long term side effects in two studies [ 32 , 33 ] and poor adherence was partly attributed to dosing regimen in five studies [ 32 , 33 , 35 37 ]. However, a recent study of MSM in Toronto found that high versus low actual HIV risk were more willing to take PrEP (OR 27.11; 95% CI, 1.33 to 554.43) [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Many studies report challenges aligning perceived risk with actual risk [ 13 , 14 , 32 34 ]. Participants described concern regarding perceived long term side effects in two studies [ 32 , 33 ] and poor adherence was partly attributed to dosing regimen in five studies [ 32 , 33 , 35 37 ]. However, a recent study of MSM in Toronto found that high versus low actual HIV risk were more willing to take PrEP (OR 27.11; 95% CI, 1.33 to 554.43) [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…More recently, in Europe, proportions of MSM willing to use PrEP have ranged from 47.8% to 54.3% in Scotland [58,59], 57.0% in Portugal [60] and 57.6 % in Spain [61]. Recent Canadian studies reported willingness to use PrEP of 55.0% [62,63]. In the US where the majority of studies on PrEP have been conducted, willingness to use PrEP has ranged from 46.1% to 71.0% [64][65][66][67][68][69].…”
Section: Discussionmentioning
confidence: 99%
“…Another barrier is that some persons with HIV risk factors do not feel sufficiently at-risk for HIV to warrant PrEP [5][6][7][8], which relates to perceptions of risk not health systems issues. Studies comparing perceptions of HIV risk against HIV risk scores showed differences in how personal risk-taking was viewed, with many believing their behaviours were "too low-risk" to warrant PrEP [9][10][11][12][13][14][15][16]. While most persons at risk for HIV agreed PrEP was important, many felt this intervention was only necessary for other higher-risk persons, not themselves [17,18].…”
Section: Introductionmentioning
confidence: 99%